A formal definition of Big Data based on its essential features. Issue 3 (4th April 2016) - De Mauro, Andrea; Greco, Marco; Grimaldi, Michele
Abstract : Purpose: – The purpose of this paper is to identify and describe the most prominent research areas connected with "Big Data" and propose a thorough definition of the term. Design/methodology/approach: – The authors have analysed a conspicuous corpus of industry and academia articles linked with Big Data to find commonalities among the topics they treated. The authors have also compiled a survey of existing definitions with a view of generating a more solid one that encompasses most of the work happening in the field. Findings: – The main themes of Big Data are: information, technology, methods and impact. The authors propose a new definition for the term that reads as follows: "Big Data is the Information asset characterized by such a High Volume, Velocity and Variety to require specific Technology and Analytical Methods for its transformation into Value." Practical implications: – The formal definition that is proposed can enable a more coherent development of the concept of Big Data, as it solely relies on the essential strands of current state-of-the-art and is coherent with the most popular definitions currently used. Originality/value: – This is among the first structured attempts of building a convincing definition of Big Data. It also contains an original exploration of the topic in connection with library management.